Diagnostic algorithm for axial involvement in psoriatic arthritis - E. E. Gubar; T. V. Korotaeva; L. D. Vorobyeva; E. Yu. Loginova; Yu. L. Korsakova; P. O. Tremaskina; A. V. Smirnov; M. M. Urumova; S. I. Glukhova (Научно-практическая ревматология)
The aim – to develop a unified diagnostic algorithm for axial psoriatic arthritis (axPsA).Subjects and methods. 122 patients with psoriatic arthritis (PsA), duration less than 10 years, were included in the study according to CASPAR (The ClASsification for Psoriatic ARthritis) criteria, provided they also had axial involvement. Axial involvement was detected in case of radiographic sacroiliitis ((rSI); bilateral grade ≥2 or unilateral grade ≥3) or SI active according to magnetic resonance imaging (MRI) (MRI-SI), or ≥1 syndesmophyte(s) of the cervical and/or lumbar spine (CS/LS), or facet joints ankyloses of the CS. Patients were evaluated for the presence of inflammatory back pain (IBP) by ASAS (The Assessment of SpondyloArthritis international Society) criteria. Back pain lasting over three months, that did not meet ASAS criteria was considered chronic back pain (chrBP). HLA-B27 antigen status was observed.Results and discussion. IBP was identified in 87 (71.3%), chrBP – in 35 (28.7%) patients, 49 (40.2%) patients had older age (>40 years) at back pain onset. 120 (98.4%) patients had peripheral arthritis, 75 (61.5%) – dactylitis, 69 (56.6%) – enthesitis, 122 (100%) – psoriasis, 90 (73.8%) – nail psoriasis. Isolated axial disease without peripheral arthritis was found in 2 (1.6%) patients. RSI was detected in 85 (69.7%) patients, in 28 of 85 (32.9%) patients rSI developed without IBP. Spinal lesions of the LS and CS were found in 100 (82.0%) patients, chunky “non-marginal” syndesmophytes – in 60 (49.2%), asymmetrical syndesmophytes of the LS – in 22 of 72 (30.6%), paravertebral ossification – in 5 (4.1%) patients. Isolated spinal lesions without rSI were found in 37 (30.3%), isolated spinal lesions without rSI or MRI-SI – in 21 (17.2%) patients. HLA-B27 was observed in 27 of 86 (31.4%) examined patients. Diagnostic algorithm for axPsA was developed. All PsA patients, regardless whether they experienced IBP/chrBP or not, must undergo diagnostic imaging: pelvis, LS and CS X-ray. In patients without rSI, MRI of the sacroiliac joints should be performed. AxPsA diagnosis must be confirmed by imaging. Axial involvement is detected in case of rSI or MRI-SI, or ≥1 syndesmophyte(s) of the CS/LS, or facet joints ankyloses of the CS.